The Museum of Paintings and the Provincial Library of Orihuela: A Project of the Provincial Commission of Monuments of Alicante (1835-1868) (BSAA arte, 2019)
In the middle of the 19th century, in the disentailed Convent of Santo Domingo of Orihuela, the first Museum of Paintings and Provincial Library was installed by the Provincial Commission of Monuments of Alicante. A task done on the grounds of the Royal Orders of 13 June and 14 July 1844 that marked one of the first milestones in the management of the historical and artistic heritage of this province. On this line, and across the documents kept in the archive of the Real Academia de Bellas Artes de San Fernando and in the Diocesan Archive of Orihuela, it is intended to reconstruct and highlight this punctual but significant historical event.
Keywords: Provincial Commission of Monuments of Alicante; Museum of Paintings; Provincial Library; Orihuela; Convent of Santo Domingo